EPIDEMIOLOGY AND CO-INFECTION ANALYSIS AMONG HIV-INFECTED INDIVIDUALS PRESENTING AT A TEACHING HOSPITAL IN BAYELSA STATE, NIGERIA - Okon, Koko; Affia, Aniekan; Adeniji, Funke; OKERENTUGBA, PHILLIP; Okonko, Iheanyi (Covenant Journal of Physical and Life Sciences, 2025)
Coinfections have a major impact on viral persistence and reservoirs in some ways. Coinfections can trigger immune cell activation, creating an environment favourable for HIV-1 persistence. This study aims to analyse the coinfection profiles of persons infected with HIV presenting at a tertiary hospital in Bayelsa State, Nigeria. A cross-sectional approach was employed in the study, and the study population was drawn from persons infected with HIV undergoing clinical monitoring at the Niger Delta University of Teaching Hospital (NDUTH), Bayelsa State, Nigeria. A whole blood sample was collected from 200 consented subjects. Serological analysis of cytomegalovirus ((CMV), hepatitis B core antibodies (HBc) IgM, and herpes simplex virus 1 &2 (HSV 1&2) was carried out using commercially available enzyme-linked immunoassay (ELISA) kits. CMV IgG was detected in 169 samples and CMV IgM in 130 samples, representing 84.5% of HIV patients with persistent CMV coinfection and 65.0% with recent coinfection with CMV, respectively. Also, HBV core IgM was detected in 48 (24.0%), HSV IgG in 114 (57.0%), and HSV-IgM in 79 (39.5%) of the samples tested among the study subjects. Also, 189 representing 94.5% of the samples tested, were positive for either CMV, HBV, HSV, or all three viruses. Overall, the information and findings of this study provided fresh insight and knowledge on the current circulating HIV-1 co-infections with CMV, HBV, and HSV 1&2. Clinicians can leverage these findings to provide more individualistic care to HIV patients for better health outcomes and a reduction in the rate of transmission in the general population.